Exploration of cyclooxygenase-2 inhibitory peptides from walnut dreg proteins based on in silico and in vitro analysis - Zishan Hong; Jing Xie; Liang Tao; Jing-Jing Dai; Tingting Li; Li Zhang; Yuying Bai; Xia Hu; Jinlian Chen; Jun Sheng; Yang Tian (Food Science and Human Wellness)
Walnut dreg protein hydrolysates (WDPHs) exhibit a variety of biological activities, however, the cyclooxygenase-2 (COX-2) inhibitory peptide of WDPHs remain unclear. The aim of this study was to rapidly screen for such peptides in WDPHs through a combination of in silico and in vitro analysis. In total, 1262 peptide sequences were observed by nano liquid chromatography/tandem mass spectrometry (nano LC-MS/MS) and 4 novel COX-2 inhibitory peptides (AGFP, FPGA, LFPD, and VGFP) were identif ied. Enzyme kinetic data indicated that AGFP, FPGA, and LFPD displayed mixed-type COX-2 inhibition, whereas VGFP was a non-competitive inhibitor. This is mainly because the peptides form hydrogen bonds and hydrophobic interactions with residues in the COX-2 active site. These results demonstrate that computer analysis combined with in vitro evaluation allows for rapid screening of COX-2 inhibitory peptides in walnut protein dregs.